Kelayakan Penerapan Pembangkit Listrik Hibrida di Bendungan Matenggeng - Evely Tirza; Doddi Yudianto; Okky Ahmad Purwana (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Indonesia’s is focusing the electricity power production from non-renewable sources to renewable energy resources. Hydropower might be promising; however, its production is highly affected by seasonal variability. Matenggeng dam is designed as multipurpose dam, namely for supplying the irrigation system, flood control, and utilization in a hydropower system. Based on its design report, the Matenggeng Dam is planned to produce power of about 11.74 MWac at water elevation of +194 m. Due to seasonal variability, the power production decreases to 5.74 MWac at the lowest water elevation. Solar energy, on the other hand, has a great potential in Indonesia, this study is aimed to optimize the decrease in existing electricity production in Matenggeng Dam by hybridization of hydropower with floating solar power plants. According to the regulation of Indonesia’s public affair only 20% of the water surface area at normal condition can be used. By taking into account the reservoir operation pattern and the reservoir various conditions, the optimum water surface area that can be used for FPV installation is 295.7 hectare. The result showed that, the solar power plant successfully produces 14 GWh of energy annually, where the monthly generation is stable at 1,200 MWh per month.